Komparasi Penerapan Model Pembelajaran Aktif Tipe Pencocokan Kartu Indeks dengan Model Ceramah Terhadap Hasil Belajar Geografi di Kelas XI IPS SMA Negeri 3 Kerinci - Yeva Lenda Mahyastuti (Journal on Education, 2022)
This study aims to find a significant difference of learning outcomes between active learning model types matching index cards and lecture method on learning outcomes geography in class XI IPS SMAN 3 Kerinci. The working hypothesis (H1) stated is "There are differences in learning outcomes of students use active learning model types matching index cards in the eye of learning geography class XI IPS SMAN 3 Kerinci". This type of research is classified in experimental research with the final data analysis method using t-test to test the differences between the mean values for the two samples. The study sample as many as 28 students for each class of two classes selected by cluster random sampling. Data were collected using a questionnaire that has been tested for validity and reliability. Data were analyzed by using the Microsoft Excel program. The findings of this study is a significant difference between the active learning model types matching index cards to student learning outcomes. Based on the above results and scores thitung 5,51 ttable of 1.71 (0.05; 26) with an average value of the index card matching method amounted to 83.93 and 79.82 by conventional methods. Based on these findings it can be concluded that the active learning model types matching index cards directly affect the outcome of learning geography students at SMAN 3 Kerinci. Implications of this research is the active learning model types matching the index card can be used as one of the models in the learning eye geografiuntuk improve learning outcomes.